Histopathological Evidence of Occipital Involvement in Male Androgenetic Alopecia - Khunkhet, Saranya; Chanprapaph, Kumutnart; Rutnin, Suthinee; Suchonwanit, Poonkiat (Frontiers in Medicine, 2021)
Background: The occipital region of the scalp is generally accepted as an unaffected area of androgenetic alopecia (AGA) for both genders. However, evidence of AGA involving the occipital scalp has been demonstrated in women; meanwhile, it is unclear whether occipital involvement also occurs in men. Objective: We aimed to determine if there is occipital involvement in men with AGA. Methods: This case-control study compared hair counts of scalp biopsy specimens from the occipital region of 82 men with Hamilton-Norwood III-VII and 82 unaffected men. Results: The mean ages of men with AGA and controls were 40.1 ± 8.9 and 38.6 ± 10.5 years, respectively (P = 0.291). A significant decrease in total hair follicles, terminal hair follicles, follicular units and terminal to vellus (T:V) ratio, along with a significant increase in follicular stelae was indicated in the AGA group compared to controls (all P < 0.05). Subgroup analyses revealed that average counts of total hair follicles, terminal hair follicles and T:V ratios were also significantly lower in males with Hamilton-Norwood VI and VII than in controls (all P < 0.05). There were no correlations between increasing age and hair count parameters, but a significant negative association was found between total follicle numbers and disease duration (r = -0.23, P = 0.02). Conclusions: AGA can involve the occipital area of male patients with advanced disease. Therefore, the occiput of particular cases should not be used to determine reference data for normal scalp hair, and preoperative measurements of miniaturized hairs in the donor site are strongly recommended in all persons undergoing hair transplantation.